2018
DOI: 10.3390/ijms19051405
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Regulation of p62 is Critical for Cancer Therapy

Abstract: Sequestosome1 (p62/SQSTM 1) is a multidomain protein that interacts with the autophagy machinery as a key adaptor of target cargo. It interacts with phagophores through the LC3-interacting (LIR) domain and with the ubiquitinated protein aggregates through the ubiquitin-associated domain (UBA) domain. It sequesters the target cargo into inclusion bodies by its PB1 domain. This protein is further the central hub that interacts with several key signaling proteins. Emerging evidence implicates p62 in the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 100 publications
3
125
0
1
Order By: Relevance
“…The level of LC3 per se indicates that autophagy is initiated, but may not reflect upon whether autophagy has proceeded or become impaired [21,31]. A proceeding autophagy implies a low level of p62 since this protein becomes degraded together with the cargo in the autophago-lysosome [32]. Thus, increased LC3 and p62 in AIH suggest that autophagosome formation has occurred without an increase in lysosomal degradation, as has been demonstrated in case of p62 in a recent study [33].…”
Section: Discussionmentioning
confidence: 89%
“…The level of LC3 per se indicates that autophagy is initiated, but may not reflect upon whether autophagy has proceeded or become impaired [21,31]. A proceeding autophagy implies a low level of p62 since this protein becomes degraded together with the cargo in the autophago-lysosome [32]. Thus, increased LC3 and p62 in AIH suggest that autophagosome formation has occurred without an increase in lysosomal degradation, as has been demonstrated in case of p62 in a recent study [33].…”
Section: Discussionmentioning
confidence: 89%
“…The results indicated that curcumin induces apoptosis by regulating PARP, c‐PARP, caspase‐9, and caspase‐3 expression, whereas THC induces autophagy by regulating p62 and LC3 expression. p62 regulates multiple signaling pathways including those that control autophagy, apoptosis, and tumorigenesis through its different domains (Fan, Yin, Zhang, & Hu, ; Islam, Sooro, & Zhang, ). Autophagy induction induces an increase in LC3‐II and a concurrent decrease in p62 (Yoshii & Mizushima, ).…”
Section: Resultsmentioning
confidence: 99%
“…While LC3-I remains in the cytosol, LC3-II is incorporated into both the outer and the inner membrane of the autophagosome, and therefore LC3-II is largely considered as a marker of autophagy induction [54]. Also, an adaptor protein sequestosome 1 (SQTM1, known as p62), which directs substrates to the autophagosomes, is degraded with its cargo proteins and can be used as a read-out of the autophagic flux [58,59]. Another conjugation system is under control of ATG7 and ATG10, and regulates the formation of the ATG5/ATG12 conjugate.…”
Section: An Overview Of Autophagy and Autophagy-dependent Cell Deathmentioning
confidence: 99%